Functionalised silica coated nanoparticle hybrids for drug delivery and imaging - Yang, Yanmei (2013)
In recent years, nanoparticles have been extensively explored for biomedical applications due to their unique properties. Among various nanomaterials, silica-based nanoparticles exhibit superior biocompatibility which attracted much research attention. These particles also provide several advantages such as large functional surface, tunable structures and high spectroscopic transparency. In this research dissertation, we focused on developing novel and convenient drug delivery systems for theranostic applications based on silica-coated nanoparticles.